Handbook of financial risk management - Roncalli, Thierry (Boca Raton, FL : CRC Press, 2020)
Developed over 20 years of teaching academic courses, the Handbook of Financial Risk Management can be divided into two main parts: risk management in the financial sector; and a discussion of the mathematical and statistical tools used in risk management. This comprehensive text offers readers the chance to develop a sound understanding of financial products and the mathematical models that drive them, exploring in detail where the risks are and how to manage them. Key Features: Written by an author with both theoretical and applied experience Ideal resource for students pursuing a master's degree in finance who want to learn risk management Comprehensive coverage of the key topics in financial risk management Contains 114 exercises, with solutions provided online at www.crcpress.com/9781138501874
1. Introduction. Part I Risk Management in the Financial Sector. 2. Market Risk. 3. Credit Risk. 4. Counterparty Credit Risk and Collateral Risk. 5. Operational Risk. 6. Liquidity Risk. 7. Asset Liability Management Risk. 8. Systemic Risk and Shadow Banking System. Part II Mathematical and Statistical Tools. 9. Model Risk of Exotic Derivatives. 10. Statistical Inference and Model Estimation. 11. Copulas and Dependence Modeling. 12. Extreme Value Theory. 13. Monte Carlo Simulation Methods. 14. Stress Testing and Scenario Analysis. 15. Credit Scoring Models. ConclusionAppendix
OCLC-licensed vendor bibliographic record.
Keywords: Financial risk management -- Handbooks, manuals, etc; Risk management -- Mathematical models -- Handbooks, manuals, etc